Catholic resistance theory: William Barclay versus Jean Boucher - Nicholls, S (Taylor and Francis, 2018)
This article examines William Barclay’s response to Jean Boucher’s De Justa Abdicatione Henrici Tertii (1589) in view of the complexities of Catholic political thought in this post-Tridentine period. It argues that Barclay’s famous category of ‘monarchomach’ is problematic for its avoidance of the issue of confessional difference, and that on questions of the relationship between the respublica and the ecclesia Barclay struggled to find an adequate response to Boucher in his De Regno et Regali Potestate (1600). His De Potestate Papae (1609) is treated as the intellectual extension of his battle with Boucher, and more broadly his confrontation with the position of the Catholic League and Jesuits on indirect papal power. By considering Barclay’s works in the context of French Gallicanism and the Catholic League in the French Wars of Religion, this discussion aims to reposition Barclay in relation to other Catholic political theorists and thereby re-evaluate the category of Catholic resistance theory.